Time interval analysis of ductus venosus and cardiac cycles in relation with umbilical artery pH at birth in fetal growth restriction - Tomoki Suekane; Daisuke Tachibana; Yasushi Kurihara; Natsuko Yokoi; Naomi Seo; Kohei Kitada; Mie Tahara; Akihiro Hamuro; Takuya Misugi; Akemi Nakano; Masayasu Koyama (BMC, 2021)
Abstract Background The aims of this study were to evaluate the time intervals of flow velocity waveforms (FVW) of ductus venosus (DV) and cardiac cycles, as well as the pulsatility index of DV-FVW (DV-PI), in correlation with umbilical artery (UA) pH at birth in fetal growth restriction (FGR) complicated with placental insufficiency. Methods Data were retrospectively retrieved from pregnancies complicated by FGR. FGR was defined as an estimated fetal weight below − 2.0 S.D. with an elevated UA-PI. Time interval assessments of DV-FVW were as follows: the duration of systolic wave was divided by the duration of diastolic wave and defined as DV-S/D. We also measured the following time intervals of ventricular inflow through tricuspid valve (TV) and mitral valve (MV): (iii), from the second peak of ventricular inflow caused by atrial contraction (A-wave) to the opening of atrio-ventricular valves and: (iv), from the opening of atrio-ventricular valves to the peak of A-wave. (iii)/(iv) was expressed as TV-S/D and MV-S/D, for TV and MV, respectively. The time interval data were transformed into z-scores. Results Thirty-one FGR fetuses were included in this study. Both DV-PI and DV-S/D showed significant correlation with UA-pH (r = − 0.677, p = < 0.001 and r = 0.489, p = 0.005 for DV-PI and z-score of DV-S/D, respectively) and more significances were observed in FGR ≤ 28 + 6 gestational weeks (r = − 0.819, p < 0.001 and r = 0.726, p = 0.005, for DV-PI and z-score of DV-S/D, respectively) than in FGR > 28 + 6 gestational weeks (r = − 0.634, p = 0.007 and r = 0.635, p = 0.020, for DV-PI and z-score of DV-S/D, respectively). On the other hand, TV-S/D and MV-S/D showed no significant correlation with UA-pH, although these z-scores indicated significant decreases compared with normal references. Conclusions Time interval analysis of DV-FVW might be a valuable parameter, as well as DV-PI, for the antenatal prediction of fetal acidemia in the management of FGR fetuses.